Connection Digitalization System Online Queues and Accessibility with Satisfaction Patient Elderly at the Community Health Center Jatibening Bekasi City in 2026 - Ariska Agustina Ariska Agustina; Tri Suratmi; Samingan (International Journal Of Community Service, 2026)
Improvement population carry on age ( elderly ) demands service quality , inclusive and responsive health care to need group age said . Digital transformation , including system online queue at the facility service health level First , it is expected increase efficiency and satisfaction patients . However , limitations digital literacy and conditions cognitive elderly potential hinder utilization . Research This aim analyze connection digitalization system online queues and accessibility service health with satisfaction patient elderly at the Community Health Center Jatibening Bekasi City in 2026.Study This use approach quantitative with cross-sectional design . Population study This is elderly in the work area Community Health Center Jatibening and population affordable is elderly people who come seek medical treatment to Community Health Center Jatibening with using visit data patient elderly January 2026. The sample study This amounting to 158 samples with use Slovin's formula . Collection technique sample done by accidental sampling. Data collected use questionnaire and analyzed in a way univariate , bivariate (Chi-Square test), and multivariate ( regression logistics multiple ).The results show majority respondents is elderly young (60.1%), educated high (88.6%), and not working (89.2%) with 78.5% stating No satisfied to system online queue . Analysis results show there is connection significant between digitalization system online queues (p=0.042; OR=3.079) and accessibility (p=0.026; OR=3.705) with satisfaction patient elderly . Accessibility elderly to system online queue is variables dominant influencing​ satisfaction patient elderly .In conclusion that digitalization system online queues and accessibility elderly relate with satisfaction patient elderly and accessibility become factor dominant , so that implementation digitalization need accompanied by improvement accessibility and approach friendly elderly